Silver nanoparticle@carbon quantum dot composite as an antibacterial agent. Issue 16 (28th March 2022) - Liu, Tianyu; Pang, Qianyue; Mai, Kang; He, Xiaoting; Xu, Li; Zhou, Feiyan; Liu, Yi
Abstract : Synthesis of AgNPs@S, N-CQDs active against bacteria. Abstract : A AgNPs@S, N-CQDs composite was synthesized by a one-step approach. It possessed AgNPs naturally surrounded by S, N-CQDs, and the size of the particles was found to be uniform and stable via a series of characterization methods. The antibacterial properties of the composite material were studied, and it had good antibacterial properties against S. aureus, E. coli, MRSA and C. albicans . The minimum inhibitory concentrations were 63 μg mL −1 against S. aureus and MRSA and 32 μg mL −1 against E. coli and C. albicans . In addition, the AgNPs@S, N-CQDs composite had an antibacterial effect via the generation of ROS, which was verified using the DCFH-DA kit. Finally, HepG2 cells were used to study its biocompatibility. The antibacterial properties and biocompatibility results show that the AgNPs@S, N-CQDs composite material can serve as a promising antibacterial agent.